F‐actin determines the time‐dependent shift in docking dynamics of glucagon‐like peptide‐1 granules upon stimulation of secretion. Issue 5 (30th January 2023) - Harada, Kazuki; Takashima, Maoko; Kitaguchi, Tetsuya; Tsuboi, Takashi
Abstract : Although exocytosis can be categorized into several forms based on docking dynamics, temporal regulatory mechanisms of the exocytotic forms are unclear. We explored the dynamics of glucagon‐like peptide‐1 (GLP‐1) exocytosis in murine GLUTag cells (GLP‐1‐secreting enteroendocrine L‐cells) upon stimulation with deoxycholic acid (DCA) or high K + to elucidate the mechanisms regulating the balance between the different types of exocytotic forms (pre‐docked with the plasma membrane before stimulation; docked after stimulation and subsequently fused; or rapidly recruited and fused after stimulation, without stable docking). GLP‐1 exocytosis showed a biphasic pattern, and we found that most exocytosis was from the pre‐docked granules with the plasma membrane before stimulation, or granules rapidly fused to the plasma membrane without docking after stimulation. In contrast, granules docked with the plasma membrane after stimuli and eventually fused were predominant thereafter. Inhibition of actin polymerization suppressed exocytosis of the pre‐docked granules. These results suggest that the docking dynamics of GLP‐1 granules shows a time‐dependent biphasic shift, which is determined by interaction with F‐actin. Abstract : The authors investigated the dynamics of glucagon‐like peptide‐1 (GLP‐1) exocytosis, and found that GLP‐1 secretion from enteroendocrine L cells (GLUTag cells) shows a time‐dependent biphasic shift after stimulation with secretagogues. In the first phase, exocytosed granules are those that were already pre‐docked with the plasma membrane, or those that immediately fused to the plasma membrane without docking. Inhibition of actin polymerization suppressed exocytosis of pre‐docked granules.